Subtitling Analysis Of Interrogative Sentence Found InTorque Movie By Bluray - Adi Mulyono, Ridwan, Dr. Dwi Haryanti, M. Hum (2017)
This research aims at 1)identify the types of interogative sentence found in Torque movie. ( 2 ) to give explanation Equivalence from the source language and target language. This research uses the collecting data from the movie and found the translation of subtitle. Source of subtitle from Bluray. The research show that there are three types of interrogative sentence found in Torque movie. There are interrogative sentence Word Question with positive question, Attached or Tag- Question and Word Question. From the analysis can be seen from 629 data has found 189 interrogative sentence include in three types above. First, there are 93 data or 42,2% belong to Interrogative Word Question, 72 data or 38% belong to interrogative Yes or No question with positive question, and 23 data or 12,1% belong to Attached or Tag question. From the analysis above can be found if from 629 data, there are 557 data which has the same translation from the source language. 72 data belong to non equivalence translation and different with the source language.